Extraction, synthesis and characterization of nickel (II) and cobalt (II) caprate complexes - Rehali, Hanane; Barkat, Djamel (Journal of Applied Engineering Science & Technology, 2017)
Liquid-liquid extraction is one of the most useful technique for selective and recovery of metal ions aqueous solutions, applied in purification processes in numerous chemical industries. In this work the liquid-liquid extraction of nickel (II) and Cobalt (II) from aqueous solution by capric acid(HL) in chloroform at 25±0.05°C has been studied. The nickel and cobalt in capric acid monomeric complexes, having formula of the type [M(HL) 2 L 2 ]  (M :Co(II) and Ni(II). The complexes have been characterized with the help of elemental analysis, the apparatus used is a laser granulometer Malvern Mastersizer Type 2000/3000, this device can measure the particle sizes, conductance measurements, electronic UV-Visible suggest that the octahedral . Fourier transform infrared confirm the presence of bidentate carboxylate in the complexes. The thermal behavior of complexes was studied by thermogravimetry (DTG), differential thermal analysis (DTA).The final decomposition products namely NiO and Co 3 O 4 .